2023
DOI: 10.1186/s13020-023-00815-8
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin protects against ulcerative colitis by inhibiting the SGK1/NLRP3 signaling pathway and reshaping gut microbiota in mice

Xiaohu Wang,
Chaozhuang Shen,
Xingwen Wang
et al.

Abstract: Background According to the Chinese Pharmacopoeia, the fruit of Schisandra chinensis (Turcz.) Baill. (SC) is an important traditional Chinese medicine that can be used to treat diarrhea. Despite the increasing research on the anti-inflammatory and anti-oxidant aspects of SC, the studies on the anti-ulcerative colitis of Schisandrin (SCH), the main constituent of SC, are relatively few. Methods The mice used in the study were randomly distributed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The modification and degradation of β -catenin are key events in the occurrence and development of colon cancer ( Zhao et al, 2022 ). The research indicates that Sishen Pills ( Zhao et al, 2019 ) and their active metabolites, schisandrin B ( Zhang et al, 2021a ), schisandrin ( Wang et al, 2023d ), evodiamine ( Kim et al, 2019 ; Shen et al, 2019 ; Ding et al, 2020 ), and rutaecarpine ( Byun et al, 2022 ) could affect cell fate by regulating the NLRP3 and Wnt signaling pathways, thus offering a therapeutic role in IBD and colon cancer.…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The modification and degradation of β -catenin are key events in the occurrence and development of colon cancer ( Zhao et al, 2022 ). The research indicates that Sishen Pills ( Zhao et al, 2019 ) and their active metabolites, schisandrin B ( Zhang et al, 2021a ), schisandrin ( Wang et al, 2023d ), evodiamine ( Kim et al, 2019 ; Shen et al, 2019 ; Ding et al, 2020 ), and rutaecarpine ( Byun et al, 2022 ) could affect cell fate by regulating the NLRP3 and Wnt signaling pathways, thus offering a therapeutic role in IBD and colon cancer.…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 99%
“…For example, schisandrin A ( Wang et al, 2023b ), schisandrin B ( Liu et al, 2015 ), schisandrin C ( Kim et al, 2022 ) and deoxyschizandrin ( Yu and Qian, 2021 ) inhibited the NF-κB nuclear translocation and downstream pro-inflammatory signaling pathway activation; schisandrin B could also regulate AMPK/Nrf2, affect NLRP3 inflammasome, and then alleviate cell pyroptosis and intestinal epithelial damage caused by immune inflammation. In addition, Wang et al conducted a pharmacokinetic analysis of seven different types of lignin in Schisandrae Chinensis and found that C max and AUC 0-∞ of schisandrin were significantly higher than those of other lignans; they also confirmed that it could treat UC by inhibiting the serum/glucocorticoid regulated kinase 1 (SGK1)/NLRP3 pathway and regulating the gut microbiota ( Wang et al, 2023d ).…”
Section: Research Progress On Metabolites Of Sishen Pill In the Treat...mentioning
confidence: 99%
“…These reactions have attracted much attention due to their ability to produce complex polycyclic structures ( e.g. natural products, pharmaceuticals, or valuable intermediates) 11–55 (Scheme 1).…”
Section: From Classical Cycloadditions To Higher-order Cycloadditionsmentioning
confidence: 99%
“…4 In particular, eight-membered nitrogen-heterocycles are regarded as compelling privileged structures for drug discovery, especially for challenging targets that are difficult to modulate by conventional small molecule screening libraries. 5–8 In general, the installment of nitrogen heteroatoms in a ring system enhances the interaction with a biological target, yielding pharmaceuticals with more potent activities. 9,10 For example, (+)-balasubramide, an eight-membered lactam isolated from Clausena indica exhibits anti-neuroinflammatory properties (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%